PUBLIC PERCEPTION OF PEDESTRIAN SPACE IN INDUSTRIAL ZONES: A CASE STUDY OF THE PULOGADUNG INDUSTRIAL ZONE - Merinda, Herlina; Hasibuan, Hayati Sari; Tumuyu, Sri Setiawati (UI Scholars Hub, 2026)
Addressing the difficulties of sustainable development, the Jakarta Industrial Estate Pulogadung encounters the challenge of becoming more inclusive in constructing infrastructure for walkers by creating paths that are friendly for pedestrians As walking serves as an important sustainable and healthful means of transport, having pedestrian pathways can enhance how the public views pedestrian accessibility in their workplace. This, in turn, can promote the use of more eco-friendly public transport options. This research aims to explore how the public views pedestrians in industrial zones, with the goal of promoting spaces that are friendly to walkers. The study utilized a quantitative method paired with a mixed-methods analysis, which comprised observations, interviews, surveys, and spatial assessments. The Walkability Index measured at JIEP was recorded as 62.46, which is categorized as